Māori nurses' experiences of the Nursing Entry to Practice Transition Programme. (December 2017) - Foxall, Donna; Forrest, Rachel; Meyer, Salome
This study captures the kōrero pūrūkau (spoken experiences/perspectives) of Māori Registered Nurses from two New Zealand District Health Boards who transitioned from undergraduate study to practice by completing the Nursing Entry to Practice Transition Programme during 2010 to 2012. The research approach was informed by Kaupapa Māori (Māori approach), and semi-structured one-to-one interviews allowed participants to share their visions, feelings, and memories. A thematic analysis of the transcribed interviews identified two main categories: (a) Work Environment, with Māori Identity, Workload, Study, and Support being the emergent sub-themes and (b) Nursing Entry to Practice Transition Programme Experiences and Perceptions, with three sub-themes, namely, Before Nursing Entry to Practice Transition Programme, During Nursing Entry to Practice Transition Programme, and After Nursing Entry to Practice Transition Programme. The findings highlighted the challenges faced by new Māori Registered Nurses during Nursing Entry to Practice Transition Programme and identified the critical importance of support during this time of change. This study may provide useful information for the future development of Nursing Entry to Practice Transition Programme in New Zealand with the aim of retaining indigenous Registered Nurses.